가스 크로마토그래피-질량 분석기를 이용한 하천의 알킬 페놀류 및 비스페놀-A의 모니터링 - 유연웅; 정봉철; 표희수; 이정애 (한국환경분석학회, 2007)
Alkylphenols, the degradation products of alkylphenol ethoxylate as surfactants, have raised public concern due to their environmental and human health effects. The present work is described for the detection of 8 alkylphenols (alkylphenols: t-butylphenol, n-butylphenol, n-pentylphenol, n-hexylphenol, t-octylphenol, n-heptylphenol, nonylphenol, and n-octylphenol) and bisphenol-A in water and dirt sample of Tan-Cheon by gas chromatography-mass spectrometry (GC-MS). The method involved solid-phase extraction (SPE) with Sep- Pak C18 and subsequent conversion to trimethylsilyl derivatives for sensitive analysis in the selected ion-monitoring (SIM) mode. The practical quantitative limits for SIM of most of the alkylphenols lower than 0.01 ng/ mL (for water) and 0.8 ng/g (for dirt). The SIM responses were linear with the correlation coefficient ranged from 0.9884 to 0.9981. When applied to samples investigated, the concentrations of t-butylphenol, bisphenol- A and nonylphenol detected were different in the range of 0.006~96.1 ppb in some samples.